The media mix - Insight Media (New York : Insight Media, 1995)
This program shows how to balance the elements of a strong campaign to serve a particular product. It discusses effective signage; message consistency; direct mail; company logos; and newspaper, radio, and television advertising
DVD format
Keywords: Advertising; Mass media and business; Mass media